Bad Heir Day - Wendy Holden (London headline, 2000)
Anna's boyfriend Seb is impossibly handsome, impossibly rich and generally just impossible. When eventually he dumps her, she vows to give up men and throw herself into her career. Which is how she ends up working for Cassandra. The social climber from hell, Cassandra has a huge house in Kensington, a philandering rock star husband and the spawn of Satan for a son. So when desperate-to-escape Anna meets dashing Jamie, charming heir to a castle in Scotland, she can't believe her luck. And she probably shouldn't...
Keywords: Chick Lit; Fiction; Romance; Contemporary; Humor